Cardiac Drugs Requirement during Off-Pump Coronary Artery Bypass (OPCAB) Surgery- A Comparison between Combined High Thoracic Epidural Anaesthesia (HTEA) with GA and GA Alone (Cardiovascular Journal, 2010)
Background: During off pump coronary artery bypass surgery (OPCAB) to provide adequate myocardial protection cardiac anaesthesiologist frequently needs to use various pharmacological intervention rather than physiological manipulation. This is challenging to overcome the adverse effects of the various drugs. During the past few years, high thoracic epidural anaesthesia (HTEA) as an adjunct to general anaesthesia has become more popular and has been shown to be potentially beneficial in patients with coronary diseases. It provides good protection from stress response, ensures hemodynamic stability, improves distribution of coronary blood flow and reduce demand for oxygen and perioperative arrhythmia. Objective: This study has been undertaken with a view to compare the requirement of intraoperative cardiac drugs between HTEA with General Anaesthesia(GA) and GA alone. Methods: Prospective, randomized case control study was undertaken in sixty patients, without having left main coronary disease, left ventreicular ejection fraction